2016
DOI: 10.1186/s12933-016-0454-x
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol remnants and triglycerides are associated with decreased myocardial function in patients with type 2 diabetes

Abstract: BackgroundRecently, genetic studies have suggested a causal relationship between cholesterol remnants and ischemic heart disease. We aimed to determine whether cholesterol remnants and its marker, triglyceride levels, are associated with cardiac function as determined by sensitive echocardiographic measures in a population of patients with type 2 diabetes.MethodsComprehensive echocardiography including 2D-speckle tracking echocardiography was performed on a representative sample of 924 patients with type 2 dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 41 publications
5
20
0
Order By: Relevance
“…The degree of contribution of dyslipidemia to LV remodeling has been debated, with evidence both for and against the predictive utility of lipid concentrations on indexes of LV structure [ 8 16 ]. Hence, the adoption of nontraditional lipid profiles to estimate altered LV morphology has fostered a growing enthusiasm.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The degree of contribution of dyslipidemia to LV remodeling has been debated, with evidence both for and against the predictive utility of lipid concentrations on indexes of LV structure [ 8 16 ]. Hence, the adoption of nontraditional lipid profiles to estimate altered LV morphology has fostered a growing enthusiasm.…”
Section: Discussionmentioning
confidence: 99%
“…Reports from observational studies on the possibility of dyslipidemia-induced LV remodeling have been inconsistent [ 8 16 ]. Several lines of evidence have demonstrated that low high-density lipoprotein cholesterol (HDL-C) may unfavorably modify LV structure in the setting of elevated LVM or presence of LVH [ 8 10 ], whereas others have not [ 11 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Remarkable is that T2DM patients receiving statin therapy in combination with increased levels of cholesterol remnants and triglycerides were associated with slight decreased in left ventricular systolic function. Targeting cholesterol remnants in addition to T2DM patients receiving statins might be beneficial on cardiac function [ 151 ]. From a clinical perspective, it was shown that many patients with T2DM and CVD did not receive lipid lowering therapy while their lipid levels were not in the optimal range [ 152 ].…”
Section: Metformin–statin Combination Therapymentioning
confidence: 99%